PENINGKATAN HASIL BELAJAR MATEMATIKA PADA MATERI TURUNAN FUNGSI MENGGUNAKAN TEKNIK PROBING PROMPTING DI KELAS XI IPA 1 SEKOLAH MENENGAH ATAS NEGERI 2 PALEMBANG - Megariati (Mathematics Education Journal, 2011)
This research is an action research, aims to find out the improvements studied mathematics through the use of learning techniques of probing- prompting, to the subject of research is the grade XI IPA 1 SMA Negeri 2 Palembang as many as 41 students, even in the first half year of 2009/2010 study from 17th April – 15th May, 2010, with the material derivative. In the implementation of this research consists of two cycles covering the stages of planning, implementation, observation and reflection. Collecting data to find out the results of the study carried out by giving a test after the learning process on each cycle progresses. While as supporting data to find out students ' activities carried out observation at the time of execution of the instruction. The results of this study showed an increase in the results of learning math, i.e. in cycle 1 average increased 65.9 class at cycle 2 be 78,8. Standard of classical learning with KKM assigned 75%, cycle 1 have not been met, namely only 68,25% However, in cycle 2 to 85,0%. Besides learning activities of students during the learning process also experienced an increase from cycle 1 to cycle 2 it shows that the technique can improve the results prompting probing learning of mathematics. The study recommends that effective techniques for prompting probing is used as an alternative teaching techniques in an attempt to improve the results of learning math students.DOI : 10.22342/jpm.5.1.822